ETNOMATEMATIKA MINANGKABAU PADA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Daswarman, Daswarman; Eddy Sutadji (JIPD (Jurnal Inovasi Pendidikan Dasar), 2022)
Minangkabau culture is rich with several mathematical concepts. These mathematical concepts are contained in Minangkabau culture such as custom houses, custom clothes, and traditional food. These mathematical concepts will make a positive contribution for learning mathematics. The purpose of this research is to determine geometric concepts in the form of two dimentional figure that can be seen from custom houses, custom clothes, and traditional food. This research is a qualitative research with an ethnographic approach. As an initial stage of research, a literature study is conducted first to determine the concept of geometry in mathematics learning. The results of this research are in the form of two dimentional figure of geometry concepts found in Minangkabau culture such as squares, rectangles, parallelogram, trapezoid, rhombus and circle. The concept of geometry in two dimentional figure will help learning two dimentional figure in Primary Schools.